Propuesta de Nuevas Centralidades Urbanas en la ciudad de Loja - Samaniego Morillo, María Gabriela (2018)
Abstract:The growth and consolidation of new urban centers in the city of Loja, requires the realization of a serious and weighted study of the new poles of development for a plot that is projected to a half million inhabitants. This study will strengthen the new urban centers. This reality forces to generate strategic projects to decentralize and recentralize the institutions and in this way, it can improve the citizen services, and urban mobility. The fundamental objective of the research focuses on making the city of Loja, an anthropocentric reality where you can remain permanently in man as the center of all urban action, architectural and landscape. In the final phase of the investigation, the data collected is evaluated to arrive accurately at the forecasts collected in order to consider the birth of the new plants in the city of Loja. The proposal was based on the city of Loja, incorporating other cities of the country as an intermediate city with an urban development, sustainable and sustainable.